A DISINFESTATION OF SAUSAGE WARES WITH HELP OF MIKROWAVES - Щербакова, Н. С.; Передера, Ж. О.; Передера, С. Б.; Лубенська, А. Ю. (Scientific Progress & Innovations, 2015)
The paper shows data of the disinfection of sausages by microwave waves. It is established that to reduce the number of microorganisms in sausage products affect mode power microwave and processing of samples. It determined that the sample processing has a significant impact on reducing the number of microorganisms in it than the selected mode power microwave. Prolonged exposure samples by microwave waves (within 3 minutes) favors reducing of more microorganisms, but the minimum time (1 minute) is sufficient to reduce the number of microorganisms sausage products of questionable freshness to assume it is not harmful to the human body after decontamination.